Efficient and Flexible Supercapacitors Assembled on Metal Spikes. Issue 8 (1st May 2015) - Fan, Xing; Fan, Zongbo; Peng, Ming; Cheng, Li; Du, Jun; Zou, Dechun; Tao, Changyuan
Abstract Lavender‐like, lightweight, and flexible supercapacitive electrodes with high specific capacitance have been fabricated for the first time by assembling petal‐like nano‐nickel oxides on nickel spikes that are grown by using a simple non‐templated method. Compared with traditional fiber‐shaped electrodes, the specific capacitance of these electrodes increases six‐fold to 4.47 F cm−2. For a 1 cm‐long spike electrode, the capacitance reaches over 1.4 F, and no evident drop is observed at a bending angle of 180°. Both the mechanical strength and large current discharging property are unexpectedly good. The spike structure makes the apparent mass density of the electrode as light as carbon fiber, and exhibits considerable potential for use in future portable energy‐storage devices.